Role of academic institutions during the COVID-19 pandemic - Neupane, Dinesh; Rai, Juna; Chaulagain, Sarita; Jha, Nisha; Sah, Anishka; Bhuju, Dinesh Raj (International Journal of Infection Control, 2020)
A novel coronavirus first reported from China has resulted in a formidable outbreak globally threatening millions of human lives with unprecedented challenges. Society needs effective information source to combat this pandemic. Academic institutions would play an important role in disseminating science-based information and planning pandemic crisis. This study aims to examine how academic institutions around the world have been working in combating COVID-19 pandemic. Two hundred and thirty three high ranking universities representing 44 countries from six continents, viz. Africa, Asia, Europe, North America, South America, and Oceania were selected and their websites visited. Any information on COVID-19 updated in the websites were noted and classified. Universities from developed world (North America, Europe) and Oceania were found to be actively disseminating up-to-date information on COVID-19 with compared to those from developing world. All universities in Oceania, 96.66% universities in North America, 96.55% in Europe, 83% in South America, 61.25% in Asia, and 56% in Africa had information regarding COVID-19 in their websites. The high income coutries were facing high casulaties of the disease, and majority of their universities (85.71%) were disseminating up-to-date information through their websites. There exists a gap between the universities of developed and developing world in disseminating COVID-19 pandemic information.